2013
DOI: 10.1007/s10509-013-1554-7
|View full text |Cite
|
Sign up to set email alerts
|

A technique for estimation of starburst masses and ages in luminous compact galaxies

Abstract: We propose a technique for estimation of the mass m of the young stellar population and the starburst age T in luminous compact galaxies (LCGs). For this purpose we use LCG Hα emission line luminosities from the Sloan Digital Sky Survey (SDSS) spectra and Galaxy Evolution Explorer (GALEX) FUV and NUV continuum luminosities. The method is intended for quick estimation of m and T in large galaxy samples and does not require spectral energy distribution (SED) fitting. Estimated m and T for the sample of about 550… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
0
5
0
7
Order By: Relevance
“…We study the temporal evolution of the radio emission at 1.4 GHz for the sample of 52 LCG galaxies. Earlier, the temporal evolution of the Hα and UV luminosities in these galaxies was studied by Parnovsky et al (2013). We estimate the luminosities of the thermal component of the radio emission from the luminosities of the Hα line emission and the luminosities of the non-thermal component.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We study the temporal evolution of the radio emission at 1.4 GHz for the sample of 52 LCG galaxies. Earlier, the temporal evolution of the Hα and UV luminosities in these galaxies was studied by Parnovsky et al (2013). We estimate the luminosities of the thermal component of the radio emission from the luminosities of the Hα line emission and the luminosities of the non-thermal component.…”
Section: Discussionmentioning
confidence: 99%
“…The mean redshift of the 1.4 GHz subsample is z = 0.074. Parnovsky et al (2013) showed that L Hα /m and L UV /m behave similarly with the starburst age T and are described by Eqs. (1) and (2) -they are constant at T ≤ T 0 and decline exponentially at T > T 0 .…”
Section: The 14 Ghz Subsamplementioning
confidence: 95%
See 3 more Smart Citations